Aculeaxanthones A–E, new xanthones from the marine-derived fungus Aspergillus aculeatinus WHUF0198 - Wu, Jun; Shui, Hua; Zhang, Mengke; Zeng, Yida; Zheng, Mingxin; Zhu, Kong-Kai; Wang, Shou-Bao; Bi, Hongkai; Hong, Kui; Cai, You-Sheng (Frontiers in Microbiology, 2023)
Introduction Dimeric natural products are widespread in plants and microorganisms, which usually have complex structures and exhibit greater bioactivities than their corresponding monomers. In this study, we report five new dimeric tetrahydroxanthones, aculeaxanthones A−E (4−8), along with the homodimeric tetrahydroxanthone secalonic acid D (1), chrysoxanthones B and C (2 and 3), and 4−4’-secalonic acid D (9), from different fermentation batches of the title fungus. Methods A part of the culture was added to a total of 60 flasks containing 300 ml each of number II fungus liquid medium and culture 4 weeks in a static state at 28˚C. The liquid phase (18 L) and mycelia was separated from the fungal culture by filtering. A crude extract was obtained from the mycelia by ultrasound using acetone. To obtain a dry extract (18 g), the liquid phase combined with the crude extract were further extracted by EtOAc and concentrated in vacuo. The MIC of anaerobic bacteria was examined by a broth microdilution assay. To obtain MICs for aerobic bacteria, the agar dilution streak method recommended in Clinical and Laboratory Standards Institute document (CLSI) M07-A10 was used. Compounds 1−9 was tested against the Bel-7402, A-549 and HCT-116 cell lines according to MTT assay. Results and Discussion The structures of these compounds were elucidated on the base of 1D and 2D NMR and HR-ESIMS data, and the absolute configurations of the new xanthones 4−8 were determined by conformational analysis and time-dependent density functional theory-electronic circular dichroism (TDDFT-ECD) calculations. Compounds 1–9 were tested for cytotoxicity against the Bel-7402, A549, and HCT-116 cancer cell lines. Of the dimeric tetrahydroxanthone derivatives, only compound 6 provided cytotoxicity effect against Bel-7402 cell line (IC50, 1.96 µM). Additionally, antimicrobial activity was evaluated for all dimeric tetrahydroxanthones, including four Gram-positive bacteria including Enterococcus faecium ATCC 19434, Bacillus subtilis 168, Staphylococcus aureus ATCC 25923 and MRSA USA300; four Gram-negative bacteria, including Helicobacter pylori 129, G27, as well as 26,695, and multi drug-resistant strain H. pylori 159, and one Mycobacterium M. smegmatis ATCC 607. However, only compound 1 performed activities against H. pylori G27, H. pylori 26695, H. pylori 129, H. pylori 159, S. aureus USA300, and B. subtilis 168 with MIC values of 4.0, 4.0, 2.0, 2.0, 2.0 and 1.0 μg/mL, respectively.